Isolation of anticancer compound of Artemisia cina hairy root and its inhibition activity on cervix cancer cells. - ., Aryanti; Ermayanti, Tri Muji; Mariska, Ika; Bintang, Maria (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
The research of isolation of anticancer agent of A.cina hairy roots and its inhibition activity on cervix cancer cells have been conducted. Hairy roots transformed by Agrobacterium rhizogenes strains A4 and ATCC-15834 were then extracted by n-hexane and separated by column chromatography with variation of n-hexane/ethyl acetate as eluent. All samples include hexane extract and result of column chromatography tested to cervix HeLa Ohio cells with concentration of 50 μg/ml for hexane extract and 10 μg/ml for column chromatography respectively. The most active fraction was then tested by the concentration of 1 to 5 μg/ml. Confirmation of transformed root of A.cina was conducted by PCR analysis. The result of experiment shown that hexane extract of hairy root, normal root ( in vitro ), leaves of plant from green house as a control gave the inhibition value were about 84 %. The most active fraction from column chromatography was fraction E with IC50 at the concentration of 1 μg/ml and inhibition value was 95 %, the identification compound of this fraction was terpenoid group. The confirmation result showed that TL-DNA was transferred by 780 kb.Key words : anticancer, hairy root, Artemisia cina.